2013
DOI: 10.1016/j.juro.2013.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Surgery after Failed Treatment of Synthetic Mesh Sling Complications

Abstract: Success after the initial failure of mesh sling complications repair is possible but multiple surgeries may be required. Each symptom should be addressed separately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 22 publications
0
43
0
Order By: Relevance
“…Blaivas et al reported a retrospective review of 47 women who had previously undergone at least 1 operation to correct MUS complications [64]. With a mean follow-up of 3 years, 72 % of patients had a successful outcome after the first procedure.…”
Section: Long-term Sequelaementioning
confidence: 99%
“…Blaivas et al reported a retrospective review of 47 women who had previously undergone at least 1 operation to correct MUS complications [64]. With a mean follow-up of 3 years, 72 % of patients had a successful outcome after the first procedure.…”
Section: Long-term Sequelaementioning
confidence: 99%
“…The effects of long-term pain receive no attention at all in any study except for a few case studies of complications. 9,[40][41][42][43][44] The concomitant, widespread use of two different generic sling designs (RP and TOT) with different implantation techniques and at least 41 different commercially available kits, 42 each having different sling and trocar characteristics with potentially different complication profiles, confounds accurate analysis of sling complications. These different characteristics might also portend different complication profiles, yet studies of sling complications almost never distinguish between the different kit types and many do not even separate TOT from RP slings.…”
Section: Smus Complicationsmentioning
confidence: 99%
“…6 Furthermore, this study 6 excluded patients whose slings were removed owing to pain and other indications, thus the actual incidence of sling removal owing to complications is probably even higher than that. Extrapolating from this estimate and the estimated number of slings implanted in the 6,9,10,41,44,[100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] Use of imperfect research methodologies, a lack of long-term follow up and reporting bias have been suggested as causes of these differences. 10,45,115,116 Safety and risk:benefit considerations Safety of SMUS surgery refers to the probability of any adverse event, while risk describes the range and probability of specific adverse events.…”
Section: Smus Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately the results of mesh removal in such individuals are mixed at best. 7,8 Indeed, Milose et al note sobering results for those individuals presenting with SUI with complex coexisting factors such as fistula or urethral erosion, of which only 3 of 8 had SUI cured with fascial sling. 6 Nevertheless, such redo cases add another layer of complexity and another category of deficiencies in individuals with SUI.…”
mentioning
confidence: 99%